Screening drug effects in patient‐derived cancer cells links organoid responses to genome alterations - Julia Jabs; Franziska M Zickgraf; Jeongbin Park; Steve Wagner; Xiaoqi Jiang; Katharina Jechow; Kortine Kleinheinz; Umut H Toprak; Marc A Schneider; Michael Meister; Saskia Spaich; Marc Sütterlin; et al. (Molecular Systems Biology)
Abstract Cancer drug screening in patient‐derived cells holds great promise for personalized oncology and drug discovery but lacks standardization. Whether cells are cultured as conventional monolayer or advanced, matrix‐dependent organoid cultures influences drug effects and thereby drug selection and clinical success. To precisely compare drug profiles in differently cultured primary cells, we developed DeathPro, an automated microscopy‐based assay to resolve drug‐induced cell death and proliferation inhibition. Using DeathPro, we screened cells from ovarian cancer patients in monolayer or organoid culture with clinically relevant drugs. Drug‐induced growth arrest and efficacy of cytostatic drugs differed between the two culture systems. Interestingly, drug effects in organoids were more diverse and had lower therapeutic potential. Genomic analysis revealed novel links between drug sensitivity and DNA repair deficiency in organoids that were undetectable in monolayers. Thus, our results highlight the dependency of cytostatic drugs and pharmacogenomic associations on culture systems, and guide culture selection for drug tests.